IMPLEMENTATION OF THE THERAPEUTIC COMMUNITY FOR CONVICTS IN INDONESIAN CORRECTIONAL INSTITUTION - Putra, Andari Rizky Aria (Department of Guidance and Counseling, FIP, Undiksha, 2020)
The increase in narcotics abuse in Indonesia has made increase of convicts. In the Correctional Institution, convicts will be given guidance in the form of Therapeutic Community as strategies to aimed and restoring the convicts as before. This study aims to describe the implementation of the Therapeutic Community in the implementation of coaching that can be a reference in the implementation of coaching in the Indonesian Correctional Institution. Implementation of the Therapeutic Community in Corrections Institutions in Indonesia must have the support of various parties in its implementation in order to run well, but in reality the field still has some obstacles in implementing the Therapeutic Community.